A gamificação e o professor reflexivo de robótica educacional: um estudo de caso - Silva Filho, Fernando Barros da (2023)
Gamification is an object of interest in the field of education because it has the potential to increase student engagement and promote meaningful learning. This work aims to investigate the presence of gamification elements in pedagogical practice in educational robotics. From a literature review, the principles of gamification that can be incorporated into classes were identified. The methodology adopted consisted of observing classes, seeking to identify whether these elements emerged spontaneously in the context. The results revealed that, even without the declared intention of the involved agents, the environment incorporates and applies gamification elements in the pedagogical practice. The incorporation occurs naturally, approaching, especially to the teacher, the profile of a game designer. Those involved establish symbiotic relationships between educational robotics and gamification, providing game-like learning experiences. Adopting these gamification elements has the potential to increase student motivation, promote collaboration, provide feedback, and create an engaging learning environment. However, it is emphasized that a conscious and reasoned understanding of gamification can further enhance these learning experiences. The implicit incorporation of gamification elements in the learning environment may be related to the contemporary sociocultural context, marked by the presence of games and digital interactions. Students develop expectations about their education, seeking an engaging, challenging, and life-relevant learning environment. Given this context, teacher training must be adapted to prepare them to navigate and benefit from these strategies. This implies the development of skills, understanding of educational principles related to gamification and reflection on pedagogical practice. It is concluded that gamification plays an important role in the pedagogical practice of educational robotics and can be an efficient strategy to engage students and promote deeper learning. However, it is necessary to invest in teacher training, training them to consciously use gamification elements in their classes, taking advantage of the potential of technology and understanding the needs of students in today's society.